Epidemiologic study of chronic kidney disease in hyperuricemia of Chengdu - GUO Zong-lin; LIAO Xue-song; WANG Qi-rong; QIAN Quan; GAO Xiang; PU Li-jun; FU Bing; SU Xiao-yu (Linchuang shenzangbing zazhi)
Objective To identify the prevalence and related risk factors of chronic kidney disease（CKD） in hyperuricemia of Chengdu.Methods 1 321 eligible samples of railway workers with hyperuricemia from Sep.2009 to Dec.2010 taken from " Health examination data of 5 326 Chengdu urban groups" were selected.These data included questionnaire（anamnesis,smoking and drinking）,somatoscopy（blood pressure,body height and body weight）,blood and urine examination indicators（blood sugar,blood lipid,blood uric acid,blood creatinine,urea nitrogen urin microalbumin/urine creatinine ratio and routine urine examination）.Analysis was based on related diagnostic criteria.There were albuminuria（urin microalbumin/urine creatinine ratio ≥30 mg/g）,reduced estimated glomerular filtration rate[eGFR<60 mL·min-1·（1.73 m2）-1]and hematuria（erythrocytes >3/HP in urinary sediment）.Results（1） Prevalence of albuminuria in the hyperuricemia group was 14.00%,prevalence of hematuria was 1.97%,prevalence of reduced eGFR was 4.69%,prevalence of CKD was18.09%,and recognition was 2.93%.Prevalence of albuminuria,reduced eGFR and CKD in the hyperuricemia group was obviously higher than in non-hyperuricemia group.Prevalence of albuminuria,eGFR and CKD in the group of hyperuricemia complicated with hyperlipidemia and/or diabetes mellitus and/or hypertension was obviously higher than simple hyperuricemia group.（2） Prevalence of albuminuria,reduced eGFR and CKD was obviously increased with 60 mol/L uric acid elevated Uricemia had a positively linear correlation with urine microalbumin/urin creatinine.Uricemia showed a negatively linear correlation with eGFR.（3） Hypertension,diabetes mellitus and BMI were independent risk factors of albuminuria.Female of hyperuricemia was independent risk factors of hematuria.Female of hyperuricemia,age and hypertension were independent risk factors of GFR reduction.Female of hyperuricemia,hypertension,diabetes mellitus and BMI were independent risk factors of CKD.Conclusions The prevalence of CKD was higher than ordinary people in hyperuricemia group of Chengdu,and is related with the level of uric acid.Control of blood pressure,blood glucose,blood uric acid,blood fat and BMI helps reduce the occurrence and development of CKD.